Finite element modelling of FRP strengthened restrained concrete slabs. (15th May 2019) - Martin, Tony; Taylor, Su; Robinson, Des; Cleland, David
Abstract: This paper considers the use of Nonlinear Finite Element Analysis (NLFEA) to predict the load capacity of a range of experimentally tested in-plane restrained reinforced concrete slabs which experienced internal arching effects under loading. The slabs were constructed at one third scale and strengthened with basalt fibre reinforced polymer (BFRP) or carbon fibre reinforced polymer (CFRP) bonded in place using the near surface mounted (NSM) technique. As the research was representative of existing floor slabs within reinforced concrete building frames, all test specimens were constructed with normal strength concrete (∼40 N/mm 2 ) and 0.15% steel reinforcement. One tenth of one percent fibre reinforced polymer (FRP) was used to strengthen samples which were compared with unstrengthened control specimens. The London University Structural Analysis System (LUSAS) finite element analysis software package was used to model all test samples using experimentally derived material test values. Experiments and NLFEA models were compared with the Queen's University Belfast (QUB) arching theory which showed that LUSAS was slightly more accurate than the QUB arching theory in predicting slab capacity. However, the QUB arching theory was found to be slightly more consistent in estimating slab capacities compared with LUSAS. Yet, both of these methods were significantly better at predicting slab capacities than existing Eurocode and American Concrete Institute codes.